Vacillations Between Discrete and Ecological Thinking: The University of Arkansas Community Design Center - Stephen Luoni (Oz, 2006)
How odd is it to devote an anthology of essays to humanitarian design? Isn’t it an oxymoron given the design professions’ tacit mission to provide human habitat? After all, professions are cultures of work distinguished by their internalization of the public good in the delivery of services and products.